2000
DOI: 10.1161/01.cir.102.21.2672-k
|View full text |Cite
|
Sign up to set email alerts
|

Dual Modulation of Cell Survival and Cell Death by β2-Adrenergic Gi and Gs Signaling in Adult Mouse Cardiac Myocytes

Abstract: There is considerable debate about the choice of intravenous platelet glycoprotein IIb/IIIa inhibitors for percutaneous coronary intervention, after a meta-analysis of 7 trials and 16,770 patients has shown a 38% reduction in death or non-fatal MI 30 days after the index procedure. At 149 hospitals in 18 countries throughout North America, Europe and Australia, 4810 patients were randomized between 12/30/99 and 8/25/00 and treated with either tirofiban or abciximab on a double-blind, double dummy basis. Clopid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 0 publications
2
32
0
5
Order By: Relevance
“…Downstream of the β 1 AR, protein kinase A (PKA) activation9,37,38 and Ca 2+ /calmodulin-dependent kinase II (CamKII) activation39,40 are known stimulators of myocyte apoptosis. On the other hand, β 2 AR coupling to Gi leads to cell survival and reduced apoptosis 10,41. As shown in our current study, the βARKct-mediated protective phenotype can be reversed by blocking β 2 AR with the addition of ICI118,551 implying a β 2 AR-Gi-dependent mechanism in play following I/R that is enhanced when GRK2 is inhibited.…”
Section: Discussionsupporting
confidence: 66%
“…Downstream of the β 1 AR, protein kinase A (PKA) activation9,37,38 and Ca 2+ /calmodulin-dependent kinase II (CamKII) activation39,40 are known stimulators of myocyte apoptosis. On the other hand, β 2 AR coupling to Gi leads to cell survival and reduced apoptosis 10,41. As shown in our current study, the βARKct-mediated protective phenotype can be reversed by blocking β 2 AR with the addition of ICI118,551 implying a β 2 AR-Gi-dependent mechanism in play following I/R that is enhanced when GRK2 is inhibited.…”
Section: Discussionsupporting
confidence: 66%
“…β 2 ARs also mediate the effects of CAs on the heart, but in a qualitatively different manner from β 1 ARs, as they can also couple to the AC inhibitory G protein (Gi) [15,19]. This dual Gs/Gi coupling has been implicated in differential β 2 AR signaling specifically concerning myocyte apoptosis as β 2 AR-Gi is cardioprotective, while this doesn’t occur with the pro-apoptotic β 1 ARs [19–21]. …”
Section: Sns Hyperactivity and Cardiac βAr Dysfunction In Hf: Role Ofmentioning
confidence: 99%
“…Three major advances in research during the last decade on the single cardiomyocyte level have demonstrated distinctly different, even opposite functional roles of two βAR subtypes in regulating cardiac structure and function: ( 1 ) dual coupling of most β 2 AR to both G s and G i proteins in cardiomyocytes [32–34]; ( 2 ) a cardiac protective role of β 2 AR signaling in improving cardiac function and myocyte viability [35, 36]; ( 3 ) PKA-independent, CaMKII-mediated β 1 AR apoptotic and maladaptive remodeling signaling in the heart [3739] (Fig. 1).…”
Section: Mechanistic Basis For Using β2 Ar For Treatment Of Chfmentioning
confidence: 99%